Quranic Tafsir as an Educational Media for Children: A Study of “Seri Tafsir Al-Qur’an Kontemporer for Kids” by Aam Amiruddin - Khofifah Alawiyah; Miski Miski (Studia Quranika, 2025)
Planting Islamic values from an early age is a fundamental aspect in the process of child education. In this context, Qur'anic exegesis plays an important role as an educative medium that not only conveys religious messages, but also shapes children's character and morals. This study aims to examine how Aam Amiruddin's Seri Tafsir Al-Qur’an Kontemporer for Kids is utilised as a medium for children's education, both in terms of the approach to delivering the material, the language used, and the educational values it contains. This research method includes text analysis, focusing on the internal components of tafsir and the systematic presentation by the author contained in the work. This analysis is done in depth to understand how the presentation of the Qur'anic tafsir becomes a relevant educational medium for children. The results show that this tafsir is compiled using simple, interesting, and dialogical language, by including illustrations, and aligning the content of the Qur'an on daily themes that are relevant to the world of children. The educational values conveyed include faith, worship, morals, and social aspects. Thus, Seri Tafsir Al-Qur’an Kontemporer for Kids proves to be an effective alternative educational media in introducing the content of the Qur'an to children in a fun and educational manner.